CEO-speeches and stock returns - Christina Bannier; Thomas Pauls; Andreas Walter (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
We analyze the market reaction to the sentiment of the CEO speech at the Annual General Meeting (AGM). As the AGM is typically preceded by several information disclosures, the CEO speech may be expected to contribute only marginally to investors' decision-making. Surprisingly, however, we observe from the transcripts of 338 CEO speeches of German corporates between 2008 and 2016 that their sentiment is significantly related to abnormal stock returns and trading volumes following the AGM. Using a novel business-specific German dictionary based on Loughran and McDonald (2011), we find a negative association of the post-AGM returns with the speeches - negativity and a positive association with the speeches - relative positivity (i.e. positivity relative to negativity). Relative positivity moreover corresponds with a lower trading volume in a short time window surrounding the AGM. Investors hence seem to perceive the sentiment of CEO speeches at AGMs as a valuable indicator of future firm performance.
urn:nbn:de:hebis:30:3-438693
Keywords: G02; G12; G14; 330; Textual Sentiment; CEO Speeches; Market Efficiency; Textual Analysis; Annual General Meeting